Advances in Sustainable Polymers Processing and Applications - Katiyar, Vimal; Gupta, Raghvendra; Ghosh, Tabli (Materials Horizons: From Nature to Nanomaterials, 2019)
This book provides a systematic overview of the processing and applications of sustainable polymers. The volume covers recent advances in biomedical, food packaging, fuel cell, membrane, and other emerging applications. The book begins by addressing different sections of biomedical application including use of carbohydrate-based therapeutics, nanohybrids, nanohydrogels, bioresorbable polymers and their composites, polymer-grafted nanobiomaterials for biomedical devices and implants, nanofibres, and others. The second part of this book discusses various processing and packaging materials for food packaging applications. The last section discusses other emerging applications, including using microbial fuel cells for waste water treatment, microfluidic fuel cells for low power applications, among others. This volume will be relevant to researchers working to improve the properties of bio-based materials for their advanced application and wide commercialization.